David Malouf: Exploring imperial textuality - Nikro, Norman Saadi (Postcolonial text, 2006)
David Malouf's novels "An Imaginary Life" and "Remembering Babylon" explore the figure of an otherness that both disrupts and eludes the familiar and habitual. Both novels situate this figure of otherness at the very edge of the cultural landscape, undermining the neat division of self and other, in effect rewriting frontier narratives of conquest and exploration. Such narratives structure their writing in terms of a journey into the wilderness or outback whereby an experience of the lack of sense and meaning serves mainly to assert the subject's capacity to express its developing understanding of the world around it. As the writing of Malouf's novels draws subjectivity to a fugitive terrain where the terms of self-understanding recede into the infinite murmur of an apparent senselessness, the figure of otherness comes to speak a language of creative self-learning. And yet this figure of otherness in An Imaginary Life tends to disappear into the folds of a Rousseauian concept of Nature that works to stage a transcendental recuperation of both self and other. Remembering Babylon does not share this romantic conception of otherness, and could be read as a rewriting of the earlier novel. Emphasis would be placed on how subjectivity comes to stage itself as the scene of a learning of the cultural landscape.